Leveraging Technological Advancements in Technical and Vocational Education and Training (TVET) Institutions in Zimbabwe: Addressing Skills Mismatch in the Technology-driven Era - Mutuke, Mathias; Katsande, Daphne Idith (European Journal of Applied Sciences, 2025)
This study focuses on leveraging technology in TVET institutions in Zimbabwe to bridge the gap between the skills taught and those required by the labor market. Adopting a pragmatic research philosophy and mixed research approach, this investigation employed questionnaires, interview guides, and observational checklists as data collection instruments. SPSSv26 was used to analyse quantitative data and thematic analysis for qualitative data. The research findings showed that the current state of technology adoption in TVET institutions revealed a low uptake, despite the presence of Internet of Things elements such as WIFI, computer labs, and assistive devices for individuals with disabilities. Challenges identified included limited funding, curriculum misalignment, resistance from staff members, limited technical support, and a lack of technological infrastructure. To overcome these challenges, the study recommends aligning the curriculum technological advances and industry needs, establishing innovation hubs for creativity and collaboration, utilizing vernacular language in science education, and incorporating assistive devices and technologies for inclusivity. Implementing these recommendations will help Zimbabwean TVET institutions overcome obstacles, bridge the technological gap, and create a more inclusive and technologically advanced education system, preparing students for the demands of the future workforce.